Interactions between tumor-associated macrophages and regulated cell death: therapeutic implications in immuno-oncology - Ge, Yifei; Jiang, Lixue; Yang, Chengru; Dong, Qingfu; Tang, Chengwu; Xu, Yi; Zhong, Xiangyu (Frontiers in Oncology, 2024)
Tumor-associated macrophages (TAMs) play a pivotal role in sculpting the tumor microenvironment and influencing cancer progression, particularly through their interactions with various forms of regulated cell death (RCD), including apoptosis, pyroptosis, ferroptosis, and necroptosis. This review examines the interplay between TAMs and these RCD pathways, exploring the mechanisms through which they interact to promote tumor growth and advancement. We examine the underlying mechanisms of these intricate interactions, emphasizing their importance in cancer progression and treatment. Moreover, we present potential therapeutic strategies for targeting TAMs and manipulating RCD to enhance anti-tumor responses. These strategies encompass reprogramming TAMs, inhibiting their recruitment, and selectively eliminating them to enhance anti-tumor functions, alongside modulating RCD pathways to amplify immune responses. These insights offer a novel perspective on tumor biology and provide a foundation for the development of more efficacious cancer therapies.